Clinical patterns and epidemiological characteristics of dermatophyte infection in Malwa region of Punjab - Gupta, Anu; ., Alisha; Saini, Ramgopal; Kaur, Sandeep (International Journal of Research in Dermatology, 2020)
Background: Although dermatophytes are found throughout the world, the most prevalent strains and the most common sites of infection vary by region. Hot, humid climates and overcrowding predispose populations to skin diseases; including tinea infections. This study highlights the clinical pattern and epidemiological characteristics of dermatophyte infection in the Malwa region of Punjab. Methods: A cross sectional prospective study was carried out over a period of two years depending on pre-structured questionnaire on a total of 272 patients clinically suspected cases with dermatophyte infection. Socio-demographic and clinical information was collected and sample was taken. The collected samples were subjected to direct microscopy with potassium hydroxide and cultured on Sabourauds dextrose agar to identify the fungal species Results: A total of 272 patients were included in the study in which 147 were males and 125 were females. Occupation wise housewives were the most affected group constituting 114 cases. Tinea corporis was the most common type found in 159 cases and Trichophyton mentagrophytes was the most common isolated fungi. Maximum number of dermatophyte cases was in the age group of 21-30 years with 69 cases. Conclusions: In current research we observed that hot and humid environment of Malwa region of Punjab increases the prevalence of fungal infection especially in the month of June to September and the occupation of people also plays an important role in prevalence of infection. We also observed that dermatophyte fungal infection is more common in adult males as compare to females.